Authors: who they are and which their responsibilities are - Lorita Marlena Freitag Pagliuca (Universidade Federal do Ceará, 2014)
Prepare an article, be accepted by the journal and be published. A happy ending of a research normally elaborated by a group of professionals. The question is: who are these people? How are they included as authors? What are their merits and responsibilities?The discussions concerning authorship are recurrent. There is a lot of literature on this theme, and authors and publishers must reflect on this. So, what makes each one, the author of an article? How to establish who the first one and the last one will be? How many can be listed as authors? Who are the contributors?